Students’ Performance in Public Examinations, Home Background and School Factors as Determinants of Performance in University Examinations in the Southwest of Nigeria (2013)
The confidence in the validity of public examination results in predicting undergraduates‟ academic ability in Nigerian universities had drastically reduced. Studies have shown divergent findings on the predictive validity of public examinations but there seem to be a dearth of studies on the cumulative predictive validity of the public examinations of students‟ achievement at the university level. This study, therefore, investigated the causal effects of Junior Secondary School Certificate Examination (JSSCE), Senior Secondary Certificate Examination (SSCE), Universities Matriculations Examinations (UME) scores, home background and school factors on the Cumulative Grade Point Average (CGPA) of first year students in selected South-west Universities. The study was an ex-post facto research. Multi-stage sampling technique was used to select the samples. Random sampling was used to select two states from the South-west while universities were clustered along public and private ownership. Two universities each were randomly selected from each cluster. Five faculties from which a department each was chosen were randomly selected. One hundred participants were randomly sampled from each department. Purposive sampling was used to select participants who graduated from secondary schools within the South-west, Nigeria. The sample was 988 first year undergraduates. Two instruments were adapted namely, Student Home Background Questionnaire (SHBQ) (r = 0.78) and School Factors Questionnaire (SFQ) (r =0.72).Records of participants‟ JSSCE, SSCE, UME and CGPA were obtained. Five research questions were answered. Data were analysed using path analytic procedures. Variations on the CGPA of students were caused by the predictors through 37 significant and meaningful pathways. Four pathways were direct while 33 were indirect. There were minimal discrepancies between the original and the reproduced correlation coefficients. The mean difference is -0.04. Among the eight variables involved in the hypothesised model, three variables: V1 (parents‟ education), V2 (parents‟ income) and V7 (SSCE results) had significant direct and indirect influence on first year CGPA of undergraduates while V3 (Home facilities), V4 (availability of physical facilities in school) and V6 (JSSCE) had indirect influence. Students’ performances in public examinations, home background and school factors cumulatively predicted students‟ performances. Furthermore, V8 (UME) had the only direct influence. The variables had the following path weights: parent education P91 = 0.147, parents‟ income P92 = 0.092, home facilities P93 = 0.064, availability of physical facilities in school P94 = 0.134, JSSCE P96 = 0.200, SSCE P97 = 0.112 and UME P98 = 0.94 Parents‟ income and parents‟ education positively determined the university undergraduates‟ performance. Parents should be encouraged to provide their wards with all needed learning materials both at home and in school to assist them improve their performances. Furthermore, government should award scholarships to indigent students to enable them purchase all the required materials for enhanced learning and the resultant improved performance. Government or the proprietors of secondary schools in Nigeria need to provide adequate infrastructure in the schools with well equipped facilities and provide competent hands to handle them